Study Of Titanium Dioxide Nanotubes And Nanoparticles For Ultraviolet Photodetection Application - Low, Kai Ti (2021)
The study was divided into two parts. The first part focused on the growth of TNTs via electrochemical anodization and their UV photodetection performance. X-ray diffraction (XRD) analysis showed that TNTs annealed and quenched using liquid N2 exhibited significant dissimilarities in the phase transition and plane dominance compared to that of air quenched. The second part of the study was focused on the growth of TNPs via sol-gel route and their UV photodetection performance. The study revealed that the sol-gel derived TNPs (anatase) exhibited notable particle size reduction up to ~60 % of commercial TiO2 after heat treatment.